Mortality Due to Meteorological Disasters in Mexico during 2000-2015 - Jáuregui Díaz, José Alfredo; Avila Sánchez, María de Jesús; Tovar Cabañas, Rodrigo (Canadian Center of Science and Education, 2019)
This document aims to examine the changes in mortality induced by several extreme weather events from 2000 to 2015 in Mexico and analyze the characteristics of the victims, as well as the demographic and geographical vulnerabilities for the development of adaptive and preventive strategies for geographies and specific population groups to minimize the effects of extreme weather. The results show that mortality from natural disasters remains unacceptably high, since most of these deaths could have been prevented. The lethality of disasters occurs not only due to exposure to a certain threat, but also due to the accumulated vulnerability of certain populations. Taking into account the results of the research, prevention programs should target men of productive ages and older adults, women in particular to girls under nine years of age and older adults, which would reduce the impact on mortality due to meteorological disasters.